Assessment of cutaneous parameters and sympathetic skin response as a non-invasive complementary diagnostic tool in psoriasis: An exploratory study - L Sundareswaran; Prabhakaran Nagendran; Senthil K Subramanian; Amudharaj Dharmalingam; Syed G Mohuiddin (Wolters Kluwer Medknow Publications, 2023)
Background: Various diagnostic tools are used to assess cutaneous psoriasis, but most of it were subjective. Sympathetic skin response (SSR), skin PH and temperature objectively measure the skin barrier functions that could aid clinicians to evaluate accurately and predict skin disease incidence even before the onset of clinical symptoms. Aim and Objectives: The study's objective was to assess the utility of cutaneous parameters (skin temperature and pH) and SSRs influencing psoriatic patients' diagnosis management and treatment compared to controls. Materials and Methods: A total of 40 healthy participants and 40 psoriasis patients aged 18 to 65 years were recruited for this study. SSR, skin temperature and pH were assessed. The psoriasis disability index (PDI) was recorded from all the patients. Data analysis was carried out using SPSS version 20.0. Results: The results shows significantly increased skin temperature, prolonged SSR latency (bilaterally) and decreased SSR amplitude (bilaterally) among patients affected with psoriasis compared to control subjects. There is a positive correlation between SSR latency with PDI and a negative correlation between SSR amplitude and PDI in psoriasis patients. Conclusion: SSR reveals sympathetic sudomotor dysfunction and increased skin temperature in psoriasis. Furthermore, there is a link between increased SSR latency and PDI, which shows that local nervous system impairment significantly contributes to the inflammatory process in psoriasis. Thus, SSR can be used as a complementary tool for the early identification and assessment of epidermal barrier integrity in psoriasis patients, along with the clinician's standard protocols.